2012
DOI: 10.3109/0886022x.2012.684555
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dialysis Modality and Membrane Flux on Quality of Life in Hemodialysis Patients

Abstract: Background: The quality of life in patients undergoing hemodialysis is significantly disturbed. There are data that hemodiafiltration (HDF) may be more effective than conventional hemodialysis in the removal of uremic toxins and may reduce frequency and severity of intradialytic and postdialysis adverse symptoms in patients. Also, some researchers suggest advantages of using high-flux membranes compared with low-flux. Objective: The aim of this study was to examine whether hemodialysis modality and membrane fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The hemodialysis study (HEMO) found no differences between patients treated with low-flux HD and high-flux HD, 22 but when the dialysis dose was increased there was a slight improvement in QoL. Altieri 23 found that QoL differed among patients receiving HD and hemofiltration due to general improvement in physical well-being; this result was also found by Beerenhout et al 24 Knezevic et al 25 showed that patients on HDF have better QoL compared with patients on HD. Additionally, comparisons of HD with hemodiafiltration have produced conflicting results: three studies suggested an improvement in QoL 25-27 but another three studies found no such differences.…”
Section: Discussionsupporting
confidence: 58%
“…The hemodialysis study (HEMO) found no differences between patients treated with low-flux HD and high-flux HD, 22 but when the dialysis dose was increased there was a slight improvement in QoL. Altieri 23 found that QoL differed among patients receiving HD and hemofiltration due to general improvement in physical well-being; this result was also found by Beerenhout et al 24 Knezevic et al 25 showed that patients on HDF have better QoL compared with patients on HD. Additionally, comparisons of HD with hemodiafiltration have produced conflicting results: three studies suggested an improvement in QoL 25-27 but another three studies found no such differences.…”
Section: Discussionsupporting
confidence: 58%
“…In the CONTRAST study, a decrease in albumin levels by 1.4% was seen after 6 months of treatment with HDF, while the levels remained stable in the HD group [36]. Another benefit of HDF could be an improved quality of life, as suggested by the results of a cross-sectional study [57]. However, in the CONTRAST study no benefits were found with respect to quality of life.…”
Section: Hdf and Hard Clinical End Pointsmentioning
confidence: 73%
“…End-stage kidney disease has a significant and deleterious impact on duration and quality of life 1, 2, 3, 4. Approximately 1.9 million patients receive renal replacement therapy worldwide 5 .…”
mentioning
confidence: 99%
“…Patients treated with HD have lower health-related quality-of-life (HRQoL) scores than the general population, and this is associated with increased morbidity and mortality 16, 17. Although some previous studies have shown an improvement in HRQoL with convective treatments compared to HD,3, 4 the largest RCT to have studied this outcome found no difference between HDF and low-flux HD 9 . Length of recovery time after dialysis is an important patient-reported outcome measure that adversely affects HRQoL, and evidence from the Dialysis Outcomes and Practice Patterns Study (DOPPS) cohort has suggested an association between longer postdialysis recovery time and increased mortality 18 …”
mentioning
confidence: 99%